2002
DOI: 10.1515/bc.2002.092
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Fibril Formation by Human Stefin B in vitro: Immunogold Labelling and Comparison to Stefin A

Abstract: The mechanism by which proteins form amyloid fibrils is of high interest to the scientific community as its understanding could resolve questions relevant to conformational diseases. The structural and energetic basis of the process is still largely unknown. The main controversial issue is the co-existence of several protein conformations. Three models for the mechanism of protein fibrillogenesis have been proposed which need to be tested by experiments. In this report, amyloid fibrils grown from human stefin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
1
23
0
1
Order By: Relevance
“…Since we were able to detect surface localization of CagH, CagI, and CagL in transmission EM experiments and flow cytometry experiments but not FESEM experiments, there are probably limitations associated with the use of these monoclonal antibodies for immunogold labeling in the context of FESEM. Specifically, the FESEM methodology requires multiple extra washing steps (a series of seven sequential ethanol dehydration steps and three liquid carbon dioxide washing steps) that are not required for transmission EM, and monoclonal antibodies often are considered suboptimal compared to polyclonal antisera for immunogold EM studies [53].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since we were able to detect surface localization of CagH, CagI, and CagL in transmission EM experiments and flow cytometry experiments but not FESEM experiments, there are probably limitations associated with the use of these monoclonal antibodies for immunogold labeling in the context of FESEM. Specifically, the FESEM methodology requires multiple extra washing steps (a series of seven sequential ethanol dehydration steps and three liquid carbon dioxide washing steps) that are not required for transmission EM, and monoclonal antibodies often are considered suboptimal compared to polyclonal antisera for immunogold EM studies [53].…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, we were not able to detect localization of CagH or CagI to pilus structures, probably due to limitations associated with the use of monoclonal antibodies for immunogold labeling in the context of scanning electron microscopy. Specifically, the FESEM methodology requires multiple extra washing steps (a series of seven sequential ethanol dehydration steps and three liquid carbon dioxide washing steps) that are not required for transmission EM, and monoclonal antibodies often are considered suboptimal compared to polyclonal antisera for immunogold EM studies [53]. Therefore, at present it is not known whether CagL localization to pili requires dissociation of CagL from CagH and CagI, or whether all three proteins eventually localize to pili.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of stefins and their mutant stability, mechanisms of folding and fibrillogenesis [1925] have demonstrated that stefin B is an amyloidogenic protein and can serve as a suitable model for studies of amyloid fibril formation [2628], amyloid-membrane interactions [2931] and amyloid-induced cytotoxicity [32,33]. …”
Section: Introductionmentioning
confidence: 99%
“…It would be interesting to see if there is any co-localisation of stefin B (lysosomal inhibitor) with various extracellular and intracellular deposits, including Aβ plaques. We have shown that polyclonal antibody labels all the forms of stefin B, including the fibrils [69]. For cystatin C, an extracellular stefin B homologue, co-deposition with amyloid beta protein in the Alzheimer's disease brain was found [70].…”
Section: Parallels With Stefin Bmentioning
confidence: 95%